Sestrin2 as a potential therapeutic target for cardiovascular diseases. (September 2020) - Gao, Anbo; Li, Feng; Zhou, Qun; Chen, Linxi
Graphical abstract: Abstract: Sestrin2 is a cysteine sulfinyl reductase that plays crucial roles in regulation of antioxidant actions. Sestrin2 provides cytoprotection against multiple stress conditions, including hypoxia, endoplasmic reticulum (ER) stress and oxidative stress. Recent research reveals that upregulation of Sestrin2 is induced by various transcription factors such as p53 and activator protein 1 (AP-1), which further promotes AMP-activated protein kinase (AMPK) activation and inhibits mammalian target of rapamycin protein kinase (mTOR) signaling. Sestrin2 triggers autophagy activity to reduce cellular reactive oxygen species (ROS) levels by promoting nuclear factor erythroid 2 (NF-E2)-related factor 2 (Nrf2) activation and Kelch-like ECH-associated protein 1 (Keap1) degradation, which plays a pivotal role in homeostasis of metabolic regulation. Under hypoxia and ER stress conditions, elevated Sestrin2 expression maintains cellular homeostasis through regulation of antioxidant genes. Sestrin2 is responsible for diminishing cellular ROS accumulation through autophagy via AMPK activation, which displays cardioprotection effect in cardiovascular diseases. In this review, we summarize the recent understanding of molecular structure, biological roles and biochemical functions of Sestrin2, and discuss the roles and mechanisms of Sestrin2 in autophagy, hypoxia and ER stress. Understanding the precise functions and exact mechanism of Sestrin2 in cellular homeostasis will provide the evidence for future experimental research and aid in the development of novel therapeutic strategies for cardiovascular diseases.